Gastrointestinal Manifestations of Dengue Fever among Children: A Multicenter Cross-Sectional Study in Bangladesh (Bangladesh Journal of Medical Microbiology, 2023)
Background: Dengue fever is an arboviral illness spread by mosquitoes and is now a major public health issue on a global scale. Unfortunately, only few studies have documented unusual clinical characteristics of dengue among children. Objective: The objective of this study was to describe the gastro intestinal manifestations of dengue infected children during 2019 dengue outbreak in Dhaka city. Methodology: This cross-sectional study was conducted at Department of Virology at National Institute of Laboratory Medicine and Referral Center, Dhaka, Bangladesh among confirmed cases of dengue fever (Children aged less than 12 years) admitted in the pediatric ward of Dhaka Medical College Hospital, Kurmitola General Hospital, Sir Sallimullah Medical College Hospital, Dr M R Khan Sishu Hospital and BSMMU in Dhaka from June 2019 to November 2019 for period of six months. Data was collected using a structured questionnaire via face-to-face interview from guardian of the children. The investigation profile was collected from their hospital records. Results: Out of confirmed 200 pediatric dengue patients, children with dengue had an average age of 9.8±2.7 years with a slight female predominance. The majority (36.5%) of the children belonged to the age group of 5 to 9 years. Among 200 patients, 42 patients diagnosed as severe Dengue according to WHO classification. Gastrointestinal symptoms were the most common associated feature, including mostly Nausea/vomiting (81.0%), abdominal pain (61.0%), ascites (29.0%), hepatomegaly (19.0%), diarrhoea (13.0%) and others. Elevation of transaminases was found in 40.0% of the children. About 30% of the patients had platelet count more than or equal to 50000 and hematocrit more than 40 was observed in 12% patients. Atypical manifestations such as acalculous cholecystitis, acute fulminant hepatitis, acute pancreatitis, parotitis, AKI and paralytic ileus were noted in small number of patients. Conclusion: In conclusion, fever with vomiting and abdominal pain are common presentations of dengue fever.Bangladesh Journal of Medical Microbiology, July 2023;17(2):66-70